Ambivalent features of consumerism ideology: philosophical aspect - E. L. Iakovleva (Russian Journal of Economics and Law)
Objective: to study the ideology of consumerism, to identify its strategic maneuvers, to analyze the consequences of their implementation, which affected the state of modern society and the existence of a personality.Methods: logical and structural analysis, system-functional approach, comparative analysis. The material for the theoretical understanding of the problem was the ideas of J. Baudrillard and E. Cassirer.Results: the study revealed that the ideology of consumerism is addressed to the mythological type of consciousness of a personality, placing emphasis on such components as a miracle and a myth of happiness, which attracts the attention of the individual. A powerful strategic force of the consumerism ideology as a transparent control over consumer society is advertising based on the myth design technology. Its constituent elements are myth and image, which are deliberately constructed. Advertising sacralizes the promoted objects, turning them into fetishes. They become the objects of worship and lust of a consumer. Through myth and image, advertising structures the psychic reality, exerting a suggestive effect on the individual as a potential buyer of the advertised objects. The transparent manipulativeness of advertising is most clearly manifested in relation to symbolic consumption. It stimulates the consumer’s buying activity through a massive attack with signs and symbols representing the brand. Through advertising, the brand is sacralized, but its semantic significance turns out to be simulated. Dependence on symbolic consumption indicates not only the status or success of an individual, but also their lack of self-sufficiency determined by the absorption with the brand and the goods/services produced by it.Scientific novelty: consists in revealing the ambivalence of the consumerism ideology, which actively exploits the mythological type of a personality consciousness, along with the rational-pragmatic one.Practical significance: consists in using the research results to form strategies for overcoming the social crisis, further studying the current state of consumer society, the consumerism ideology, the advertising and myth design technology, as well as for forecasting the algorithms of individual actions and the possibility of correcting their worldview.